Oud neg.nr. 59281-59354. 'SVV-oorden (Koger Hoop, Turkse Tent., Kupersoord, Egmond, Dellenhove, Reggehuis, Slenaken)' - Haas, Joh. de, (1959)
Oud neg.nr. 59281-59354. 'SVV-oorden (Koger Hoop, Turkse Tent., Kupersoord, Egmond, Dellenhove, Reggehuis, Slenaken)'.